Peran Guru dalam Pembinaan Karakter Siswa Sekolah Dasar - Humaira, Sofwa Zahrotul (PGSD STKIP PGRI Pacitan, 2022)
The implementation of character education development cannot be separated from the role of the teacher. In accordance with the existing problems, the formulation of this research is how the role of teachers in efforts to develop the character of third grade elementary school students, obstacles, and solutions to overcome them. This type of research was descriptive qualitative. The subject were five elementary school teachers. The time of the research was before the Covid-19 pandemic (SDN Ploso I, 2018) and during the Covid-19 pandemic (SDN 1 Jetiskidul, 2021). Data were collected through interview and documentation techniques. Furthermore, triangulation and data analysis were carried out with the stages of data reduction, then data presentation, verification and drawing conclusions. The first result is that the character of elementary school students is developed through the role of the teacher as a caregiver, role model, and mentor. Second, teachers experience obstacles from student factors, parents, the environment, and the influence of social media. Based on these obstacles, a solution is made in the form of intensive interactive communication with parents, increasing habituation, teacher example, mentoring, and conditioning in learning activities.